Corporate ethics for turbulent markets : executive response to market challenges - Mascarenhas, Oswald (Emerald Publishing Limited, 2019)
The ebook edition of this title is Open Access, thanks to Knowledge Unlatched funding,and freely available to read online. Corporate executives immersed in the turbulent markets of today face a world not of clear cut moral dilemmas such as right or wrong, or good or evil, but instead must confront large corporate grey areas of lesser good, lesser evil, less true, less unfair, and less unjust. Often these choices become almost indistinguishable. Corporate Ethics for Turbulent Markets: Executive Response to Market Challenges sets out a universal moral foundation of corporate executive ethics. Its chapters attempt to extend the discussion on human dignity to its practical applications, map out strategic approaches for responding to current turbulent markets, and drill moral skills for taming and tapping current turbulent markets. The book features modern techniques of critical thinking, moral reasoning, moral judgment, and moral justification, and charts how to uphold stakeholder rights and duties and understand corporate moral responsibilities. Written as a guide for corporate executives who strive daily not only to be legal in all they decide, choose and do, but to also be ethical, moral, and even spiritual, the book provides skills and insights that are urgently needed to fathom and capitalize upon in the turbulent markets of today.
Keywords: Management -- Moral and ethical aspects.; Business ethics.; Business & Economics -- Organizational Behavior.; Organizational theory & behaviour.; elektronické knihy; electronic books